Small Medium Enterprise in Melaka entering international market / Hayati Abd Jalil - Abd Jalil, Hayati (Faculty of Business and Management, 2011)
The strategic thrust of Malaysian SME development is clearly to enhance SME competitiveness in the regional and global arena. The objective of this research paper was done is to identify the factor that challenges small firm in Melaka to enter international market. Design of this study is questionnaires distributed to SME entrepreneur in Melaka area. Findings of this study are key to the success of Melaka Small Medium Enterprise (SMEs) to enter international market will be capabilities depends significantly on high level of SME entrepreneur managerial , source of financing and technology availability. Research limitation will be researcher hardly finds commitment from respondent to answer the questionnaire and give quick feedback upon the questionnaires distributed. Value of this study was the expansion market of SME in Melaka will somehow contribute to state and country economical stability. Therefore, it is important for the state government plays their role and focuses these factors in order to enhance Melaka SME performance in international arena.